Economic Order Quantity Modeling using Automatic Identification Technologies - Jones, Erick; Gnaneswaran, Vettrivel; Mulfur, Walter; Armstrong, Harrison (International Journal of Supply Chain Management, 2013)
Automatic identification technologies (AIT) such as barcodes and radio frequency identification (RFID) are commonly used in inventory management. However, these AITs have operational limitations due to their system reliability with respect to the transponder or tag readability. This research introduces a model for a system reliability approach that evaluates the impact of AIT system on economic order quantities (EOQ).  We introduce the model with deterministic demand and then we introduce a real-world application that demonstrates the model’s usage for NASA’s International Space Station (ISS).  The information for the described scenario is derived from research funded by NASA EPSCOR.  Results indicate that AIT, specifically RFID, system reliability have a significant impact on the cost for sending, storing, and consuming inventory on ISS operations and other weight driven and expensive operations.